2000
DOI: 10.1128/jvi.74.21.10081-10095.2000
|View full text |Cite
|
Sign up to set email alerts
|

The E1∧E4 Protein of Human Papillomavirus Type 16 Associates with a Putative RNA Helicase through Sequences in Its C Terminus

Abstract: Human papillomavirus type 16 (HPV16) infects cervical epithelium and is associated with the majority of cervical cancers. The E1 ∧ E4 protein of HPV16 but not those of HPV1 or HPV6 was found to associate with a novel member of the DEAD box protein family of RNA helicases through sequences in its C terminus. This protein, termed E4-DBP (E4-DEAD box protein), has a molecular weight of 66,000 (66K) and can shuttle between the nucleus and the cytoplasm. It binds to RNA in vitro, including the major HPV16 late tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 60 publications
1
40
0
1
Order By: Relevance
“…16E1^E4 was expressed either by transfection using the pMV11.16E1^E4 plasmid (Davy et al, 2002) or infection using the rAd16E1^E4 plasmid (Doorbar et al, 2000). LLKLL was expressed by infection using the rAd16E1^E4LLKLL plasmid (Wang et al, 2004).…”
Section: Protein Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…16E1^E4 was expressed either by transfection using the pMV11.16E1^E4 plasmid (Davy et al, 2002) or infection using the rAd16E1^E4 plasmid (Doorbar et al, 2000). LLKLL was expressed by infection using the rAd16E1^E4LLKLL plasmid (Wang et al, 2004).…”
Section: Protein Expressionmentioning
confidence: 99%
“…Nuclei were stained using DAPI (4-6-diamidino-2-phenylindole) (Sigma). For immunoblotting, 16E1^E4 was detected using TVG402 (Doorbar et al, 2000) and GAPDH using MAB374 (Chemicon). The ubiquitin antibodies Sc-8017 (Santa Cruz) and Z0458 (DAKO) were used for immunoblotting and immunofluorescence microscopy, respectively.…”
Section: Antibodiesmentioning
confidence: 99%
“…They are made in terminally differentiated squamae that are keratin-rich, and it has been suggested that E4 may contribute to virus release by perturbing the cytokeratin network and increasing cell fragility. In addition to interacting with cytokeratins, E4 also binds to a DEAD-box protein (12). The function of this association is not yet clear, largely because the function of this DEAD-box protein is poorly defined.…”
mentioning
confidence: 99%
“…Se postula que durante esta etapa se aseguraría que el ADN viral se distribuya difusamente por las células basales proliferantes y que al mantener un número reducido de copias se impediría la activación de la respuesta inmune (17). Las células basales proliferantes migran a los estratos parabasal y espinoso, amplificándose la expresión de genes virales tempranos a través de la región no codificante (URR), los cuales permiten producir ADN a cientos de copias por célula (18); ésta etapa en el ciclo viral es conocida como la fase vegetante, proliferante o productiva (19). En este proceso de replicación del ADN viral participan un grupo de proteínas, cuyas características principales se mencionan a continuación.…”
Section: Documentosunclassified